Factors Influencing Residential Mobility In Penang Island, Malaysia - Fattah, Hamizah Abdul (2017)
Moving house in a short distance, within inter or intra urban city, are known as residential mobility which postulates the stage on residential area and households events. Residential mobility occurs when an adjustments of housing needs are made by the inhabitants to accommodate changes during family life cycle phases. Residents shifts homes because the mismatch between needs and preference which implies dissatisfaction perceives to current home. These dissatisfaction and changes over the time leads to residential preference which lead to search at desired housing characteristics in the future. Subsequently, disequilibrium housing consumption triggers residents to leave.